Pengaruh Aksi Damai 212 Terhadap Abnormal Return Saham Pada Kelompok Indeks Saham LQ45 - Verawaty Verawaty; Andrian Noviardy; Muhammad Salindra (MBIA, 2018)
Demonstration action 212 has had a negative impact on the movement of JCI, including the property sector. Based on the analysis of One-Sample t Test data, significant ifferences in mean abnormal returns before and during the events of peaceful action 212, and significant differences inmean abnormal returns after and during the events of peaceful action 212 could be interpreted that peaceful action events contained information about future benefits. Based on the analysis of Paired Sample t-Test data showed no significant difference between abnormal return of stock before and after the events of peaceful action 212. The absence of significant difference due to average abnormalreturn obtained by investors before the events of peace action 212 was greater than the average abnormal returns earned investors after the events of peaceful action 212.